Annotated list of amphibians and reptiles of Costa Rica: The role of the Museum of Zoology in cataloging the country’s herpetological diversity - Sasa, Mahmood (2025)
Introduction: The herpetological collection of the Museum of Zoology at the University of Costa Rica (MZUCR) has been key to safeguarding a sample of the diversity of amphibians and reptiles of Costa Rica and to keeping the catalog of the species present in the country up to date. This unit develops phylogenetic and biogeographic studies on these animals and plays an important role in taxonomic decisions about them. Objectives: In this work, we review and update the list of amphibians and reptiles of Costa Rica, commenting on cases with some taxonomic controversy. In addition, we briefly account for the MZUCR herpetological collection and explore its history. Methods: We update the list of present species based on identifying specimens kept in our collection and reviewing relevant scientific literature. In addition, we compile the information available in internal documents and scientific publications to establish the history of the collection. Results: We recognized 221 species of amphibians and 257 species of reptiles in Costa Rica, representing 17 and 36 families, respectively. More than 99% of amphibian species and 97% of reptiles are represented in our collection, which currently has more than 24,000 properly cataloged specimens. The collection houses 39 holotypes and 190 paratypes of 47 species, demonstrating its key role in taxonomic studies of the local herpetofauna. Although amphibian and reptile sampling cover almost the entire country, the northern lowlands and the Caribbean foothills of the Talamanca Mountain range require more significant collecting efforts. Conclusions: Despite its long and intense history of biological exploration, records of Costa Rica's herpetological diversity continue to increase. Much of this growth is a result of efforts made at the MZUCR. Since its origin as a modest private collection in the early 1960s, it has grown into one of the most comprehensive collections of amphibians and reptiles inhabiting Costa Rica. It also functions as a research unit that generates substantial biological knowledge about both groups.